Chapter 34: Pepper Production in Florida - Stephen M. Olson; Eric H. Simonne; William M. Stall; Kenneth L. Pernezny; Susan E. Webb; Timothy G. Taylor; Scott A. Smith; Darrin M. Parmenter (EDIS)
This document is HS732, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.